Tumor growth suppression by the combination of nanobubbles and ultrasound. Issue 3 (9th March 2016) - Suzuki, Ryo; Oda, Yusuke; Omata, Daiki; Nishiie, Norihito; Koshima, Risa; Shiono, Yasuyuki; Sawaguchi, Yoshikazu; Unga, Johan; Naoi, Tomoyuki; Negishi, Yoichi; Kawakami, Shigeru; Hashida, Mitsuru; et al.
Abstract : We previously developed novel liposomal nanobubbles (Bubble liposomes [BL]) that oscillate and collapse in an ultrasound field, generating heat and shock waves. We aimed to investigate the feasibility of cancer therapy using the combination of BL and ultrasound. In addition, we investigated the anti‐tumor mechanism of this cancer therapy. Colon‐26 cells were inoculated into the flank of BALB/c mice to induce tumors. After 8 days, BL or saline was intratumorally injected, followed by transdermal ultrasound exposure of tumor tissue (1 MHz, 0–4 W/cm 2, 2 min). The anti‐tumor effects were evaluated by histology (necrosis) and tumor growth. In vivo cell depletion assays were performed to identify the immune cells responsible for anti‐tumor effects. Tumor temperatures were significantly higher when treated with BL + ultrasound than ultrasound alone. Intratumoral BL caused extensive tissue necrosis at 3–4 W/cm 2 of ultrasound exposure. In addition, BL + ultrasound significantly suppressed tumor growth at 2–4 W/cm 2 . In vivo depletion of CD8 + T cells (not NK or CD4 + T cells) completely blocked the effect of BL + ultrasound on tumor growth. These data suggest that CD8 + T cells play a critical role in tumor growth suppression. Finally, we concluded that BL + ultrasound, which can prime the anti‐tumor cellular immune system, may be an effective hyperthermia strategy for cancer treatment. Abstract : The combination of intratumoral nanobubble injection and ultrasound (US) exposure caused extensive tissue necrosis.